SPIRITUALITY IN POETRY OF PHILIP LARKIN - Martina Girsang; Dian Elizabeth Octavia Nababan; Kevin Gideon Barus; Meylin Mutiara Panjaitan; Sri Melawati Hutasoit (Media Bina Ilmiah, 2023)
This study explores the elements of spirituality in the poetry of Philip Larkin. Through a close analysis of selected poems, the study reveals how Larkin's use of vivid and memorable imagery, themes that explore the transience of life and the inevitability of death, and a deep sense of awe and reverence for the world around us, infuses his poetry with a spiritual dimension. The themes of death and the transience of life, as explored in Larkin's poetry, are central to many religious and spiritual traditions, and his exploration of these themes can be seen as an expression of his own spiritual beliefs. Additionally, Larkin's use of imagery creates a powerful emotional connection between the reader and the poet, and invites us to reflect on our own experiences and emotions, and to explore the spiritual connections that exist within us all. In conclusion, Philip Larkin's poetry is a powerful expression of spirituality, and serves as a testament to the power of language and imagery to evoke deep emotions and memories, and to reveal the spiritual connections that exist within us all.